The Austronesian Origin Myths of Aboriginal Taiwan - Gauss, Valdis (CV Wahana Publikasi, 2025)
The new book “The Formosan Primary Anthropogonic Myths, Genesis and the Creation of Man” by Valdis Gauss was published in June by Brill’s Series in Taiwan Studies. This monograph offers never-before-seen insights into the origin traditions of Austronesian Taiwan. With the objective of creating the first ever English language corpus of the Formosan origin myths, over 100 texts were translated from Japanese, German and Mandarin into English and added to the over 250 total Formosan texts found for the work. This incredibly colorful array of creation texts, genesis texts, and drift origin texts sheds light on a previously rarely explored subject. The sacred oral histories of Taiwan’s Aboriginal tribes memorialize various types of vessels, of both the cosmic and non-cosmic sort that ferried the ancestors of Austronesian Taiwan to the island. Many of these cosmic vessels are said to have made loud and distressful sounds as they crashed from the sky. Moreover, embedded within the texts are the motives for the creation of man, interdictions bestowed upon the protoplasts by the creator gods, curious specters of creation en masse, the growing of mankind from seeds and an examination of modern practices that are inspired by the view of life through the lens of myth. Creation en masse themes indicate that multiple people were contemporaneously created which negates the otherwise obligatory incest motif that is required in traditions that describe the creation of a single person or two people. Correlations between the Sumerian creation myth and the Kanakanavu creation myth are also explored. Throughout the book, all of Taiwan’s Aboriginal primary anthropogonic myths are anthologized and the salient motifs preserved therein are identified.